Minithoracotomy versus Sternotomy for Mitral Surgery in Patients with Chronic Renal Impairment: A Propensity-Matched Study. Issue 5 (June 2013) - Tang, Paul; Onaitis, Mark; Desai, Bhargavi; Gaca, Jeffrey G.; Milano, Carmelo A.; Stafford-Smith, Mark; Glower, Donald D.
Objective: Compared with median sternotomy, a right thoracotomy (RT) approach to mitral surgery is associated with decreased postoperative acute renal failure. Therefore, we examined propensity-matched patients with chronic renal impairment to compare outcomes. Methods: A retrospective review at a single institution identified patients who underwent mitral valve surgery from 1986 to 2010. After excluding patients who had procedures that were not usually performed through an RT approach, 2306 patients were identified. Of this group, we found 446 patients with preoperative creatinines of 1.3 mg/dL or greater. Using propensity score matching based on comorbidities, operative year, and surgeon, 90 matched patients in each group were included. Results: There was no difference in the median year of operation. Postoperative mortality is 20% lower for the RT group ( P = 0.037) using Mantel-Cox statistics. This greater survival in the RT group occurred early within the first year and was maintained on long-term follow-up. The RT approach was also associated with a Cox proportional hazard for mortality of 0.528 ( P = 0.006). Incidence of postoperative complications with an RT approach was lower in terms of acute renal failure (10% vs 21%, P = 0.05), stroke (1% vs 9%, P = 0.017), and permanent pacemaker insertion (3% vs 11%, P = 0.044). Right thoracotomy was associated with lower chest tube outputs (503 vs 1333 mL, P < 0.001). Conclusions: The RT approach was associated with lower postoperative mortality and morbidity in patients with impaired renal function. The RT approach to the mitral valve may be preferred in this high-risk population.